2020
DOI: 10.3389/fpsyt.2020.00367
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stress and Mineralocorticoid Receptor Haplotypes in the Development of Symptoms of Depression and Anxiety During Adolescence

Abstract: Adolescence is a critical developmental period characterized by heightened levels of depressive and anxiety symptoms. Experiencing chronic or environmental stress, for example, as a result of traumatic events or insensitive parenting, increases the risk for depression and anxiety. However, not all adolescents develop depressive or anxiety symptoms following environmental stressors, due to differences in stress resilience. One of the factors involved in stress resilience is enhanced functionality of the mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Both our raw and modeled data show an overall increase for depressive symptoms in late adolescence, which is in line with previous studies using the same dataset that have shown an increase in internalizing symptoms in late adolescence for boys and girls ( 56 58 ). In the study by Nelemans et al ( 57 ), the results for girls showed a larger intercept and less steep incline in depressive symptoms in late adolescence compared to boys.…”
Section: Discussionsupporting
confidence: 91%
“…Both our raw and modeled data show an overall increase for depressive symptoms in late adolescence, which is in line with previous studies using the same dataset that have shown an increase in internalizing symptoms in late adolescence for boys and girls ( 56 58 ). In the study by Nelemans et al ( 57 ), the results for girls showed a larger intercept and less steep incline in depressive symptoms in late adolescence compared to boys.…”
Section: Discussionsupporting
confidence: 91%
“…MR is a high-affinity corticosteroid receptor that acts in synergy with the glucocorticoid receptor (GR) to mediate the molecular stress response. Both GR and MR belong to a gene co-expression cluster with peak expression in puberty and adulthood; however, whereas GR is widely expressed in the brain and peak in cerebellar tissue, MR expression peaks in limbic tissues, in accordance with previously published reports [147] . MR plays a well-documented and sex-biased role in stress resilience and depression [148] , where a functional MR haplotype protects against depression following early life trauma [149] .…”
Section: Corticosteroid Receptorssupporting
confidence: 90%
“…Previous studies reported that the anxiety symptoms are frequently found to coexist with depression symptoms. 39 , 40 An epidemiologic study found that in patients with lifetime MDD, 59% of patients experienced at least one lifetime anxiety disorder. 41 Therefore, considering the high prevalence of comorbid anxiety disorder and MDD, we did not exclude the MDD patients with anxiety disorder in this study, which might enhance the generalizability of our conclusion.…”
Section: Discussionmentioning
confidence: 99%